Enhancing Foreign Language Enjoyment and Well-Being Through a Mindfulness Based Intervention Program in the Efl High School Classroom - Teacher's Insights - Sharon Fayerberger (Babes-Bolyai University, 2023)
This paper presents findings from research that aimed to see how a mindfulness-based intervention program in an EFL high school classroom can enhance student's foreign language enjoyment and well-being. Students from a 10th grade EFL class in a high school in Israel, participated in a mindfulness-based intervention program held during a ninety-minute EFL lesson each week over a period of thirteen weeks. The research employed qualitative methodology to collect and analyze student's perception of their English studies, their feeling of well-being in the classroom and their foreign language enjoyment. Semi-structured interviews were used for fourteen participants in the program who were interviewed at two points in time: during the program and a week after the program had ended.  Additionally, insights emerging from my teacher's log, which documented the process of the mindfulness program at the end of each lesson are also discussed and shed light on future pedagogical implications. All of the participants interviewed reported on an increased level of enjoyment and well-being as well as perceiving an improvement in their EFL learning.